Looking at My Own Face: Visual Processing Strategies in Self–Other Face Recognition - Chakraborty, Anya; Chakrabarti, Bhismadev (Frontiers in Psychology, 2018)
We live in an age of ‘selfies.’ Yet, how we look at our own faces has seldom been systematically investigated. In this study we test if the visual processing of the highly familiar self-face is different from other faces, using psychophysics and eye-tracking. This paradigm also enabled us to test the association between the psychophysical properties of self-face representation and visual processing strategies involved in self-face recognition. Thirty-three adults performed a self-face recognition task from a series of self-other face morphs with simultaneous eye-tracking. Participants were found to look at lower part of the face for a longer duration for self-face compared to other-face. Participants with a more distinct self-face representation, as indexed by a steeper slope of the psychometric response curve for self-face recognition, was found to look longer at upper part of the faces identified as ‘self’ in relation to those identified as ‘other’ indicating self-other face representation may have an influence on how we recognise self-other faces visually. We also investigated the association of autism-related traits with self-face processing metrics since autism has previously been associated with atypical self-processing. The study did not find any self-face specific association with autistic traits, suggesting that autism-related features may be related to self-processing in a domain specific manner.